Essential oils and their individual components in cosmetic products - Guzmán, Eduardo (2021)
The current consumer demands together with the international regulations have pushed the cosmetic industry to seek new active ingredients from natural renewable sources for manufacturing more eco-sustainability and safe products, with botanical extract being an almost unlimited source of these new actives. Essential oils (EOs) emerge as very common natural ingredients in cosmetics and toiletries as a result of both their odorous character for the design and manufacturing of fragrances and perfumes, and the many beneficial properties of their individual components (EOCs), e.g., anti-inflammatory, antimicrobial and antioxidant properties, and, nowadays, the cosmetic industry includes EOs or different mixtures of their individual components (EOCs), either as active ingredients or as preservatives, in various product ranges (e.g., moisturizers, lotions and cleanser in skin care cosmetics; conditioners, masks or antidandruff products in hair care products; lipsticks, or fragrances in perfumery). However, the unique chemical profile of each individual essential oil is associated with different benefits, and hence it is difficult to generalize their potential applications in cosmetics and toiletries, which often require the effort of formulators in seeking suitable mixtures of EOs or EOCs for obtaining specific benefits in the final products. This work presents an updated review of the available literature related to the most recent advances in the application of EOs and EOCs in the manufacturing of cosmetic products. Furthermore, some specific aspects related to the safety of EOs and EOCs in cosmetics will be discussed. It is expected that the information contained in this comprehensive review can be exploited by formulators in the design and optimization of cosmetic formulations containing botanical extracts.